Noise Parameter Analysis of SiGe HBTs for Different Sizes in the Breakdown Region. (12th October 2016) - Lee, Chie-In; Lin, Yan-Ting; Lin, Wei-Cheng
Abstract : Noise parameters of silicon germanium (SiGe) heterojunction bipolar transistors (HBTs) for different sizes are investigated in the breakdown region for the first time. When the emitter length of SiGe HBTs shortens, minimum noise figure at breakdown decreases. In addition, narrower emitter width also decreases noise figure of SiGe HBTs in the avalanche region. Reduction of noise performance for smaller emitter length and width of SiGe HBTs at breakdown resulted from the lower noise spectral density resulting from the breakdown mechanism. Good agreement between experimental and simulated noise performance at breakdown is achieved for different sized SiGe HBTs. The presented analysis can benefit the RF circuits operating in the breakdown region.